ADMINISTRATIVE JUSTICE IN FRANCE. BETWEEN SINGULARITY AND CLASSICISM - H. Flavier; Ch. Froger (BRICS Law Journal, 2016)
The administrative justice in France oscillates between classicism and singularity. Multiple factors explain how administrative justice has come to occupy a particular place in French administrative law. Administrative justice has not only settled disputes between administration and private persons, but as well, built the French administrative law. One of the main tasks during 19th and 20th century consisted in strengthen the independence from the executive branch and the efficiency in order to satisfy the idea of good justice. Many reforms have been led since the 1990’s. That is why we propose to depict the French system and evaluate the activity of French administrative justice concerning the judicial organization, its jurisdiction and the remedies before the administrative judge. We will enlighten also our paper with a comparative approach and some statistical elements.